The Appearance of the Viennese Classicism in the Music Textbook and Music Listening Materials of The National Textbook Publisher for the Sixth Grade of Primary School (Training and Practice : Journal of Educational Sciences, 2014)
In Hungary, primary school pupils learn about the different periods of music history, the lives of the great composers and their masterpieces in the music lessons. The age of Viennese Classicism is represented in the curriculum of the 6th grade. What do children of today learn about Haydn’s, Mozart’s, Beethoven's life and work? First, I looked into the curriculum. Then I analysed the music coursebook of the National Textbook Publisher. Finally, I listened to the related music on the disc (CD). I found that the period of Viennese Classicism and its music is emphasised both in the curriculum and the textbook as well as on the disc. Pupils can get sufficient information about the life and the work of these three great composers.